2021
DOI: 10.1038/s41598-021-94933-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and spatial distribution of adult human corneal cell subtypes

Abstract: Bulk RNA sequencing of a tissue captures the gene expression profile from all cell types combined. Single-cell RNA sequencing identifies discrete cell-signatures based on transcriptomic identities. Six adult human corneas were processed for single-cell RNAseq and 16 cell clusters were bioinformatically identified. Based on their transcriptomic signatures and RNAscope results using representative cluster marker genes on human cornea cross-sections, these clusters were confirmed to be stromal keratocytes, endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 81 publications
3
38
2
Order By: Relevance
“…In this study, we performed concurrent scRNA-seq analyses of three human iPSC-derived cornea organoids and full-thickness central corneas from three different adult human donors. Our human corneal dataset corroborated recent transcriptomic studies of the full thickness human cornea ( 10 , 44 ). Human cornea organoids have not been analyzed at the single cell transcriptomic level.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we performed concurrent scRNA-seq analyses of three human iPSC-derived cornea organoids and full-thickness central corneas from three different adult human donors. Our human corneal dataset corroborated recent transcriptomic studies of the full thickness human cornea ( 10 , 44 ). Human cornea organoids have not been analyzed at the single cell transcriptomic level.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, due to the development of the technology of single-cell RNA sequencing and single-cell quantitative real-time PCR, researchers were able to analyze limbal epithelial cells at the single-cell level. Many studies were performed on human corneas from healthy and keratoconus samples and suggested more than one clusters (heterogeneity) as putative limbal stem/progenitor cells with characteristic markers [16][17][18][19]. The studies using human samples provided more human/clinical related data but have the disadvantages of significant sample variation due to the non-uniform genetic background of different donors, which makes it difficult to compare the data from different donors (e.g., among healthy corneas, between healthy corneas and pathological corneas).…”
Section: Introductionmentioning
confidence: 99%
“…On the ocular surface, the cornea is a unique and highly specialized tissue that is avascular and transparent in order to allow light to be transmitted for vision. Recent studies have identified cell types in the cornea using scRNA-seq; however, they primarily paid attention to epithelial and stromal cells, the major cell types in the cornea ( 19 , 25 , 26 ). In this study, we concentrated on the immune cell types and observed seven distinct immune cell clusters that differed in function.…”
Section: Discussionmentioning
confidence: 99%